Quality of Life of Patients with Squamous Cell Carcinoma of the Head and Neck Receiving High-Dose Cisplatin Chemotherapy and Radiotherapy. Issue 6 (June 2015) - Visacri, Marília Berlofa; Ferrari, Graziele Baldan; Dias, Pâmela; Pimentel, Rafaela; de Souza, Cinthia Madeira; Costa, Anna Paula Lourenço; de Carvalho Pincinato, Eder; Lima, Carmen Silvia Passos; Mazzola, Priscila Gava; Moriel, Patricia
<x xml:space="preserve">Abstract</x> Objectives The aim of this study was to evaluate the quality of life (QOL) of patients with squamous cell carcinoma of the head and neck before and during treatment with high-dose cisplatin and radiotherapy. Methods This was an observational and longitudinal prospective study conducted from June 2011 to March 2013 at the clinical oncology ambulatory unit of a public teaching hospital in São Paulo, Brazil. The University of Washington Quality of Life Questionnaire was used to measure the QOL of patients before and after each chemotherapy cycle with high-dose cisplatin (80–100 mg/m2, three cycles) and radiotherapy (2 Gy, 5 days/week for 7 weeks). Data were analyzed using Student t tests, and P < 0.05 was considered statistically significant. Results Thirty-two patients completed the three cycles of treatment. The study population consisted primarily of white men with a mean age older than 50 years, who had a partner, a low education level, and who were heavy smokers and drinkers, Karnofsky Performance Status of 90% to 100%, pharynx tumors, and stage IV cancer, classified as T4 and N2 stages; the minority of them required interventions such as a feeding tube and tracheostomy. We observed a reduction in QOL after treatment initiation; this reduction was significant after the second chemotherapy cycle and the sixth week of radiotherapy. The abilities to taste, swallow, salivate, and participate in activities and recreation were affected significantly. We also observed a significant improvement in pain and anxiety resulting from the chemoradiation. Conclusions Healthcare providers need to be aware of the affected domains to provide improved QOL, well-being, and security to cancer patients who are receiving this type of treatment.